Implementasi Kesiapsiagaan PT Daya Radar Utama dalam Menghadapi Risiko Bencana - Suroso, Tego; Utama, Diar Budi; Wilopo, Wilopo; Sumantri, Siswo Hadi (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2020)
The implementation of the policy is not just discussing the problem of implementing the decision, but further the implementation of the policy discusses the actualization step which is more interactive between the government and the community. Disaster preparedness is one of the important concerns in non-natural preparedness, namely minimizing the risk of technological failure on ships. Oftentimes news of ship accidents occur because of technological failures and the unreadiness of personnel to provide facilities in the ship production process. The purpose of this study is to examine the implementation of PT DRU's preparedness in dealing with disaster risks. In general, PT DRU has not yet collaborated with various disaster agencies to anticipate the occurrence of major disaster risks. The responsiveness of PT DRU through HSE as a unit that handles disaster preparedness on an internal basis shows the organization's lack of progress in increasing the capacity of personnel and completeness of safety facilities. In the organizational unit it shows that HSE was formed when PT DRU was established because of the importance of disaster risk management units by optimizing disaster preparedness through training.